A test of strangeness quantum number conservation in proton-proton collisions - Christian Bierlich; Stefano Cannito; Valentina Zaccolo (European Physical Journal C: Particles and Fields)
Abstract The study delves into the production of (multi-) strange hadrons in proton-proton collisions at LHC. Novel observables are proposed to distinguish between Epos4, based on core-corona separation between a thermalised QGP phase and a vacuum phase with global strangeness conservation, and Pythia 8.3, based on microscopic interactions between Lund strings that conserve strangeness locally. Correlations between a $$φ $$ ϕ meson and (multi-)strange hadrons are shown to be an excellent discriminator between the two types of models.